Gênero, conflito e liderança feminina na cidade pós-clássica: a atuação de Eudóxia e Olímpia sob o episcopado de João Crisóstomo (397-404) - Furlani, João Carlos (2017)
In this dissertation, we aimed to investigate, within the Roman Empire, the role of aristocratic women as important political leaders in the Eastern Capital, Constantinople. As a specific clipping, we selected a remarkable episode for the History of the Church, the conflict erupted after the deposition of John Chrysostom, in 404, in which supporters and enemies of the bishop faced each other, creating an unparalleled situation in which two important female figures emerged: Eudoxia, empress of the East; and Olympias, a deaconess of the church of Constantinople. We argue that both the active participation of Eudoxia and Olympias in the conflict that led John Chrysostom to exile as well as the feminine activity in daily situations, as in the exercise of ascetic ideals, in charitable practices through financial donations, in liturgical assistance, among other activities that provided visibility to the female element, demonstrate that women, as historical subjects, intervened in various spheres of political, social and religious life. Moreover, as benefactors of charitable works, their resources were converted into buildings and monuments associated with the Christian ethos, so that through their performance they contributed to the remodeling of the landscape of the post-classical city. We also sought to deepen our understanding of the context of exile of John Chrysostom, focusing on the relationship maintained by the deposed bishop with Olympias. In conducting the research, we explored an extensive documentary repertoire that incorporates the Dialogue on the Life of St. John Chrysostom, of Palladius; the Ecclesiastical History, of Socrates and Sozomen; the New History, of Zosimus; the Funerary Speech for John Chrysostom and the Life of Olympias, both by anonymous authorship; and the correspondence of exile sent by John to Olympias, called Letters to Olympias. We also use material culture, especially the coins minted by or in honor of Eudoxia. All these documents allowed us to reflect about the image and political performance of the women of the aristocracy and on the way in which they could interfere in the dynamics of Constantinople at the beginning of the fifth century.